Role of cardiovascular magnetic resonance in the guidelines of the European Society of Cardiology - von Knobelsdorff-Brenkenhoff, Florian (J Cardiovasc Magn Reson, 2016)
BACKGROUND: Despite common enthusiasm for cardiovascular magnetic resonance (CMR), its application in Europe is quite diverse. Restrictions are attributed to a number of factors, like limited access, deficits in training, and incomplete reimbursement. Aim of this study is to perform a systematic summary of the representation of CMR in the guidelines of the European Society of Cardiology (ESC). METHODS: Twenty-nine ESC guidelines were screened for the terms “magnetic”, “MRI”, “CMR”, “MR” and “imaging”. As 3 topics were published twice (endocarditis, pulmonary hypertension, NSTEMI), 26 guidelines were finally included. MRI in the context of non-cardiovascular examinations was not recognized. The main CMR-related conclusions and, if available, the level of evidence and the class of recommendation were extracted. RESULTS: Fourteen of the 26 guidelines (53.8 %) contain specific recommendations regarding the use of CMR. Nine guidelines (34.6 %) mention CMR in the text, and 3 (11.5 %) do not mention CMR. The 14 guidelines with recommendations regarding the use of CMR contain 39 class-I recommendations, 12 class-IIa recommendations, 10 class-IIb recommendations and 2 class-III recommendations. Most of the recommendations have evidence level C (41/63; 65.1 %), followed by level B (16/63; 25.4 %) and level A (6/63; 9.5 %). The four guidelines, which absolutely contained most recommendations for CMR, were stable coronary artery disease (n = 14), aortic diseases (n = 9), HCM (n = 7) and myocardial revascularization (n = 7). CONCLUSIONS: CMR is represented in the majority of the ESC guidelines. They contain many recommendations in favour of the use of CMR in specific scenarios. Issues regarding access, training and reimbursement have to be solved to offer CMR to patients in accordance with the ESC guidelines.